Tris-hydroxymethylaminomethane (THAM): a novel organocatalyst for a environmentally benign synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles - Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2015)
simple, efficient and environmentally benign protocol has been developed for the one-pot, multicomponent synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles using a commercially available, inexpensive, non-toxic, and biodegradable tris-hydroxymethylaminomethane (THAM) as a novel organocatalyst. Ambient reaction conditions, wide scope, avoidance of conventional isolation as well as purification techniques and the reusability of the catalyst for five consecutive runs have improved the practical utility of this multicomponent reaction protocol manifold.